Spinal Cord Drift after Non Instrumented Posterior Cervical Laminectomy. Issue 1 (April 2016) - Kharrat, Khalil; Sebaaly, Amer; Moussa, Ronald
Objective: To assess the mean value of spinal cord drift after laminectomy for cervical spondylitic myelopathy and its relation to preoperative alignment and postoperative neurologic recovery rate. Materials and Methods: 35 patients with a mean age of 62 were operated for cervical spinal myelopathy (CSM) by laminectomy with evaluation of preoperative and postoperative MRI (Min 6 months). Functional outcome was measured (Japanese Orthopedic Association score (JOA), Nurick score, and recovery rate) and radiological analysis was also made (Cobb angle and postoperative cord migration). The mean follow up period was 58.7 months Results: The mean preoperative JOA score was 11.3 and the mean postoperative JOA score was 14.6 with a mean recovery rate of 63%. The Nurick score went from 2.11 to 0.65 with a recovery rate of 69%. The postoperative cord migration was 3.82 mm. Younger age, more than four level laminectomy were correlated with better prognosis. While spinal cord drift to more than 3 mm was correlated with better outcome and to the extent of the laminectomy Conclusion: Cervical laminectomy is an indirect way of relieving the anterior compression since it allows posterior spinal cord displacement while widening of the canal. This displacement is greater when lordosis rather than kyphosis is present with positive correlation with neurological outcome.